Kawasaki disease: Shedding light on a mysterious diagnosis. Issue 7 (July 2020) - Galuppo, Jana; Kowker, Alexandra; Rolfs, Jenna; Nicholas, Joyce; Schmidt, Eric
Abstract : ABSTRACT: Kawasaki disease is an acute systemic febrile vasculitis of medium and small arteries, most often occurring in children under age 5 years. This condition is the most common cause of acquired heart disease in children in the developed world. The cause is unclear but is thought to be a hyperimmune reaction to an infectious agent. Diagnosis is clinical; the classic presentation includes persistent fever, lymphadenopathy, oral mucosal changes, conjunctivitis, and rash. Although the disease technically is self-limiting, treatment with IV immunoglobulin (IVIG) and high-dose aspirin is necessary to prevent cardiac complications, such as coronary artery aneurysm, pericarditis, or myocarditis. This article reviews the pathophysiology, clinical presentation, diagnosis, and treatment of Kawasaki disease.